Higher Levels of ANGPTL5 in the Circulation of Subjects With Obesity and Type 2 Diabetes Are Associated With Insulin Resistance - Alghanim, Ghazi; Qaddoumi, Mohamed G.; Alhasawi, Nouf; Cherian, Preethi; Al-Khairi, Irina; Nizam, Rasheeba; Alkayal, Fadi; Alanbaei, Muath; Tuomilehto, Jaakko; Abubaker, Jehad; Abu-Farha, Mohamed; Al-Mulla, Fahd (Frontiers in Endocrinology, 2019)
Objective: The family of angiopoietin-like proteins (ANGPTLs) is composed of eight ANGPTLs members that are involved in regulating various metabolic processes and have been implicated in type 2 diabetes (T2D) and obesity. ANGPTL5 is an understudied member of this family that has been suggested to regulate triglyceride metabolism with a potential role in obesity. This study was designed to investigate the expression levels of ANGPTL5 protein in the circulation of subjects with obesity and T2D. Methods: A total of 204 subjects were enrolled in this cross-sectional study, of which 95 had diagnosed T2D and 109 did not (non-T2D). Within the non-T2D group, 39 subjects were obese (BMI ≥ 30 Kg/m2) and 70 were not (BMI < 30 Kg/m2). Among subjects with T2D, 61 were obese and 34 were non-obese. Circulating ANGPTL5 plasma levels were measured by enzyme-linked immunosorbent assay (ELISA). Results: In this study, we showed that ANGPTL5 levels were higher in the plasma of subjects with T2D (mean ± standard error of the mean [SEM]: 5.78 ± 2.70 ng/mL) compared with individuals without T2D (mean ± SEM: 4.42 ± 2.22 ng/mL; P < 0.001). Obese and non-T2D subjects had significantly higher levels of ANGPTL5 (mean ± SEM: 5.115 ± 0.366 ng/mL) compared with non-obese, non-T2D subjects (mean ± SEM: 4.02 ± 0.271 ng/mL; P = 0.003). Similarly, among subjects with diagnosed T2D, those who were obese had higher ANGPTL5 plasma levels than non-obese subjects, although this difference did not reach statistical significance (P = 0.088). Correlation analyses revealed that ANGPTL5 levels positively associated with fasting plasma glucose (FPG), glycated hemoglobin (HbA1c), triglycerides (TGL) and insulin resistance as measured by HOMA-IR. Conclusion: Our data shows for the first time that circulating ANGPTL5 levels were higher in obese individuals and those with T2D. Further analysis will be required to better understand the interaction between ANGPTL5 and other metabolic related biomarkers to shed more light on its role in diabetes and obesity.